Association of Irisin Plasma Levels with Anthropometric Parameters in Children with Underweight, Normal Weight, Overweight, and Obesity. (3rd May 2017) - Elizondo-Montemayor, Leticia; Silva-Platas, Christian; Torres-Quintanilla, Alejandro; Rodríguez-López, Carlos; Ruiz-Esparza, Guillermo U.; Reyes-Mendoza, Eric; Garcia-Rivas, Gerardo
Abstract : The correlations between irisin levels, physical activity, and anthropometric measurements have been extensively described in adults with considerable controversy, but little evidence about these relationships has been found in children. The objective of this study is to correlate the plasma levels of irisin in underweight, normal weight, overweight, and obese children with anthropometric parameters and physical activity levels. A cross-sample of 40 children was divided into the following groups on the basis of body mass index (BMI) percentile. The correlations of plasma irisin levels with physical activity, anthropometric, and metabolic measurements were determined. Plasma irisin levels (ng/mL) were lower for the underweight group (164.2 ± 5.95) than for the normal weight and obese groups (182.8 ± 5.58; p < 0.05 ). Irisin levels correlated positively with BMI percentile (0.387), waist circumference (0.373), and fat-free mass (0.353; p < 0.05 ), but not with body muscle mass (−0.027). After a multiple linear regression analysis, only BMI percentile (0.564; p < 0.008 ) showed a positive correlation with irisin. Our results indicated no association with metabolic parameters. A negative correlation with physical activity was observed. Interrelationships among body components might influence irisin levels in children.